Espaços de cultura enquanto convocadores biopolíticos: a cultura se comunica como ação e não como adjetivo - Fingermann, Elisa Touchon (2019)
can, therefore, produce forms of socialization that fissure the neoliberal ways of living together, permanently supported by the stimulus to a sort of competition in which the success of one depends on the failure of another. The hypothesis with which the project investigates this matter, is that there are certain practices of communication with the environment (city, spectators, neighborhood and artistic means) that can make cultural spaces understand themselves as spaces of culture, and as a consequence become mediators of an important and urgent transformation in the ways of living in society. In order to constitute themselves as agents of biopolitical convocations, the spaces of culture must practice a powerful approach between art and everyday life. Aiming to investigate the forms of communication that make this type of social activity viable, we will present two cultural spaces that have chosen, as a criterion of performance, to have a communication management that prioritizes the environments in which they are located. Both performances in the field of Performing Arts (dance, acting and performance), between 2017 and 2019, compose the corpus of this project. One of these spaces is Casa do Povo, located in Bom Retiro neighborhood, and the other, Fazendinhando, is located in Jardim Colombo, in the south of São Paulo. These spaces were chosen because they operate in different ways in terms of occupation, management and communication of their activities, and their relationship with the environment, and thus, they can also represent other cultural spaces which are similar to them and located at other addresses. The theoretical foundation brings together the “Corpomidia” Theory (GREINER and KATZ); the concept of common, by Dardot and Laval (2017); the concept of culture, by Eagleton (2009); the proposed biopolitical convocation, by Prado (2013); the concepts of 'Government of Self and Others' by Foucault (1983), and 'immunity and community', by Esposito (2002, 2009), Negri and Hardt (2012); and the understandings of Gielen (2015) on the effects of neoliberalism in the artistic fields. Following the theoretical-investigative methodology, which brings together bibliographical review and field research, this project aimed to formulate arguments that structure cultural spaces as spaces of culture in their commitment to their surroundings. The strength of communication tends to strengthen what is being communicated, and when this communication relies on the transformative power of relations with the environment, it changes the embedded understanding of what democratization of access is, reconfiguring the citizen's ties to culture and artistic production. In times of hygienist political discourses about the public space, it becomes imperative to rethink the strength of communication in cultural spaces in the City of São Paulo